Peningkatan Hasil Belajar Siswa Melalui Metode Pembelajaran Student Facilitator And Explaining Pada Siswa Kelas VIIA SMP Negeri 4 Barebbo Kecamatan Barebbo Kabupaten Bone - Rasyid, Andi Tabrani; Ilham, Ilham (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Abstrack. The main problem in this study is how to apply the Student Facilitator And Explaining learning method to improve learning outcomes for opportunities in class VIIa of SMP Negeri 4 Barebbo, Barebbo District, Bone Regency. This study aims to improve learning outcomes with the Student Facilitator And Explaining learning method in class VIIa of SMP Negeri 4 Barebbo, Barebbo District, Bone Regency. The research procedure includes planning, implementing actions, observing and reflecting. The subjects in this study were 18th grade students of SMP Negeri 4 Barebbo, Barebbo, Bone Regency, consisting of 6 boys and 12 girls. The results showed that in the first cycle the average value obtained was 66.38 while in the second cycle the average value obtained was 81.3. Changes in attitudes, attendance, activity, self-confidence and seriousness of students participating in teaching and learning activities also showed an increase. This can be seen from the results of observations during the learning process. Based on the results of the research above, it can be concluded that the learning outcomes of Class VIIa students of SMP Negeri 4 Barebbo, Barebbo District, Bone Regency through the application of the Student Facilitator And Explaining learning method have increased.